Let's analyze the steps provided to find the error in solving the equation \(-3(4-x) + 2 = x + 2\).
Starting Equation:
\[ -3(4 - x) + 2 = x + 2 \]
Step 1:
Distributing \(-3\):
\[ -12 + 3x + 2 = x + 2 \]
Combining terms on the left side gives:
\[ -10 + 3x = x + 2 \]
Correction to Step 1:
The correct transition to the next step after combining -12 and +2 is:
\[ 3x - 10 = x + 2 \]
Step 2:
Rearranging gives:
\[ -10 + 3x = x + 2 \]
Now, move \(x\) to the left side:
\[ 3x - x = 2 + 10 \]
This results in:
\[ 2x = 12 \]
Step 3:
Now we can solve for \(x\):
\[ x = 6 \]
Summary of Errors:
- The error in Step 1 is where the expression \(3x - 10\) should have been derived correctly, rather than jumping to an incorrect equation.
- Steps afterward have also misled to an incorrect path, as there was a mistake in combining like terms and rearranging the equation.
Final Answer:
The correct solution to \(-3(4-x) + 2 = x + 2\) yields \(x = 6\). Hence the final answer should reflect \(x = 6\) rather than \(x = -2\).